Risk of coexisting endometrial carcinoma in case of atypical endometrial hyperplasia diagnosed on total hysteroscopic resection. (August 2016) - Pivano, Audrey; Crochet, Patrice; Carcopino, Xavier; Cravello, Ludovic; Boubli, Léon; Agostini, Aubert
Abstract: Objective: To evaluate the rate of coexisting endometrial carcinoma or atypical endometrial hyperplasia (AEH) residue in patients who had a total hysteroscopic resection with diagnosis of AEH and without suspicious lesions detected during hysteroscopy. Study design: This retrospective bicentric study included patients diagnosed with AEH on hysteroscopic resection products, and who subsequently underwent secondary hysterectomy. Cases of hysteroscopic appearance suggesting an endometrial carcinoma were excluded. Histopathological results of hysterectomy specimen determined the persistence or absence of AEH and the possible presence of coexisting endometrial carcinoma. Results: Thirty-two patients were selected. Histopathological analysis of hysterectomy specimens diagnosed an absence of AEH in 24/32 (75%) subjects, an AEH residue in 6/32 (18.8%) subjects and a coexisting endometrial carcinoma in 2/32 (6.2%) subjects. Conclusion: The risk of missing an endometrial carcinoma in patients diagnosed with AEH based on total hysterocopic resection is low when there is no suspicious hysteroscopic aspect, but this risk cannot be entirely excluded. Total hysteroscopic resection may be a possible alternative to hysterectomy in patients with AEH who refuse hysterectomy or are a high surgical risk. These patients require a close and long term follow-up due to the risks of residual lesion.